Investigation of some basic thermodynamic properties of Na-K alloy - Malan, Rajesh C; Vora, Aditya M (BIBECHANA, 2021)
Investigation of thermodynamic of liquid binary alloys using pseudopotential theory is reported. The potential suggested by Fiolhais et al. with its individual parameters is used for the entire calculation. A transferability of the potential from the solid to liquid medium is achieved for the presently reported binary alloy. The internal energy components, Helmholtz free energy, entropy, and total energy at various proportions of the participating alkali metals are included in the study. The comparison with the other data has been shown in the present article. Exchange and correlation effect is also tested with the help of various local field correction functions.BIBECHANA 18 (2) (2021) 1-8